Table of Content - - (Journal of natural sciences, life and applied sciences, 2024)
Table of Content: 1. Taxonomic Revision of Hibiscus (Malvoideae) of Malvaceae sensu lato in Toor Al-Baha District, Lahej Governorate, Yemen Othman Saad Saeed Al-Hawshabi 2. Environmental Impacts of Climate Change: A Comperehensive Review of Causes, Manifestations, and Solutions Sleem Ali Kreba 3. Floristic Composition, Life-forms and Chorotypes of Plants for Extended Area from Aqan to Al-Erais, Lahej Governorate, Yemen Mazen Alawi Ali Salim Atif, Ahmed Mohammed Moqbal Al-Super, Othman Saad Saeed Al-Hawshabi